Paleogene Sediment Character of Mountain Front Central Sumatra Basin - P. A. Suandhi; M. Rozalli; W. Utomo; A. Budiman; A. Bachtiar (Indonesian Journal on Geoscience, 2013)
DOI: 10.17014/ijog.v8i3.164The SE-NW trending Mountain Front of Central Sumatra Basin is located in the southern part of the basin. The Mountain Front is elongated parallel to the Bukit Barisan Mountain, extending from the Regencies of North Padang Lawas (Gunung Tua in the northwest), Rokan Hulu, Kampar, Kuantan Singingi, and Inderagiri Hulu Regency in the southeast. The Palaeogene sediments also represent potential exploration objectives in Central Sumatra Basin, especially in the mountain front area. Limited detailed Palaeogene sedimentology information cause difficulties in hydrocarbon exploration in this area. Latest age information and attractive sediment characters based on recent geological fieldwork (by chaining method) infer Palaeogene sediment potential of the area. The Palaeogene sedimentary rock of the mountain front is elongated from northwest to southeast. Thickness of the sedimentary unit varies between 240 - 900 m. Palynology samples collected recently indicate that the oldest sedimentary unit is Middle Eocene and the youngest one is Late Oligocene. This latest age information will certainly cause significant changes to the existing surface geological map of the mountain front area. Generally, the Palaeogene sediments of the mountain front area are syn-rift sediments. The lower part of the Palaeogene deposit consists of fluvial facies of alluvial fan and braided river facies sediments. The middle part consists of fluvial meandering facies, lacustrine delta facies, and turbidity lacustrine facies sediments. The upper part consists of fluvial braided facies and transitional marine facies sediments. Volcanism in the area is detected from the occurrence of volcanic material as lithic material and spotted bentonite layers in the middle part of the mountain front area. Late rifting phase is indicated by the presence of transitional marine facies in the upper part of the Palaeogene sediments.